Research Advances in the Use of Bioactive Compounds from Vitis vinifera By-Products in Oral Care - Cătălina Bogdan; Anca Pop; Sonia M. Iurian; Daniela Benedec; Mirela L. Moldovan (MDPI AG, 2020)
Oral health is considered an important factor of general health and it contributes to the quality of life. Despite the raising awareness of preventive measures, the prevalence of oral health conditions continues to increase. In this context, a growing interest in investigating natural resources like Vitis vinifera (V. vinifera) phenolic compounds (PhCs) as oral health promoters has emerged. This paper aims to review the evidence about the bioactivities of V. vinifera by-products in oral health. Up to date, a high number of studies have thoroughly reported the antimicrobial and antiplaque activity of V. vinifera extracts against S. mutans or in multi-species biofilms. Moreover, the bioactive compounds from V. vinifera by-products have been shown to modulate the periodontal inflammatory response and the underlying oxidative stress imbalance induced by the pathogenic bacteria. Considering these beneficial effects, the utility of V. vinifera by-products in the maintaining of oral health and the necessary steps towards the development of oral care products were emphasized. In conclusion, the high potential of V. vinifera by-products could be valorized in the development of oral hygiene products with multi-target actions in the prevention and progression of several oral conditions.